Hematopoietic cell transformation by a murine recombinant retrovirus containing the src gene of Rous sarcoma virus. - Pierce, J H (1984)
A recombinant murine retrovirus (MRSV) containing the src gene of avian Rous sarcoma virus (RSV) was shown to induce hematopoietic colonies in infected mouse bone marrow. MRSV-induced colony formation followed single-hit kinetics and required mercaptoethanol in the agar medium. Cells from the colonies induced by MRSV could be established as continuous cell lines that demonstrated unrestricted self-renewal in vitro and tumorigenicity in vivo. The transformants, all of which expressed high levels of the Rous sarcoma virus transforming protein, pp60src, appeared to be at an early stage in lymphoid cell differentiation. They lacked Fc receptors and detectable immunoglobulin mu heavy chain synthesis, markers normally associated with committed B cells. The majority of the MRSV-transformed cell lines contained high levels of terminal deoxynucleotidyl transferase, an enzyme present in lymphoid progenitor cells committed to the T-cell lineage. One cell line expressed Thy-1 antigen, but none expressed Lyt-1 and Lyt-2, markers of more differentiated T cells. These findings demonstrate that the src gene is capable of transforming cells of hematopoietic origin.